A one-pot method to prepare a ZnO/Ag/polypyrrole composite for zinc alkaline secondary batteries1. Issue 43 (14th May 2015) - Huang, Jianhang; Yang, Zhanhong
<x xml:space="preserve">Abstract</x> A ZnO/Ag/polypyrrole (ZAP) composite was synthesized by a facile one-pot method in which silver ammonia complex ions were reduced to metallic silver using a pyrrole monomer as the reducing agent. Meanwhile, the pyrrole monomer was oxidized and formed polypyrrole.